DETERMINANTS OF CREDIT RISK – THE CASE OF SERBIA - Jović, Željko (Economic Annals, 2017)
This paper examines systemic and specific factors that increased the credit risk level in the Serbian banking sector between 2008 and 2014, by applying the vector autoregression model (VAR), logit and probit. Business cycle and RSD depreciation are the most important systemic determinants of credit risk in the corporate sector, while in the retail sector these determinants represent a deterioration of the business and financial situation, based on a rise in the unemployment rate and nonperforming loans, together with domestic currency depreciation and the effects of the solidarity tax. Banks that entered the crisis with a lower level of capital, higher level of portfolio concentration in their 50 biggest borrowers, and with restrictions on the owner supporting the bank by providing additional capital in the period of credit risk increase, have been more exposed to default and more inclined to overestimate their good assets in their reports. The influence of RSD depreciation and the economic interrelation of clients represent an increase in the credit risk level.